HUBUNGAN PENGGUNAAN CHROMEBOOK DENGAN MINAT BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN INFORMATIKA DI SMP IT DARUL ABROR - Maulana, Ihpad; Syahrul Falah, Rivan; Ahmad Rodian, Aceng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is grounded in the digital transformation of education, which has encouraged the use of Chromebooks as a learning medium, particularly in the Informatics subject. This study aims to determine the level of Chromebook use, the level of students' learning interest, and whether there is a significant relationship between Chromebook use and learning interest among eighth-grade students at SMP IT Darul Abror. A quantitative correlational method was employed. The population consisted of all 58 eighth-grade students at SMP IT Darul Abror in the 2025/2026 academic year, and total sampling was applied so that the entire population served as the sample. Data were collected through questionnaires measuring Chromebook use (X) and learning interest (Y), and were analyzed using the Pearson Product Moment correlation test with IBM SPSS version 26. Descriptive analysis showed that both Chromebook use and students' learning interest fell into the very good category. However, the correlation test yielded a coefficient of 0.010 with a significance value of 0.942 (> 0.05), leading to the acceptance of H0 and rejection of H1. Thus, no significant relationship was found between Chromebook use and learning interest. This finding suggests that students' learning interest is likely influenced more by other factors beyond technology use, such as teachers' instructional strategies, intrinsic motivation, the learning environment, and parental support.